Impact of Layoff Announcements on the Market Value of the Firm - Gunderson, Morley; Verma, Anil; Verma, Savita (Relations industrielles / Industrial Relations, 1997)
In this study, we analyze the effect of layoff announcements on the market's valuation of firms. The event study methodology is applied to a sample of 214 announcements of layoffs made by major Canadian firms that traded on the Toronto Stock Exchange over the period 1982-1989. The main results are: (1) The market responds to the news of layoffs in a negative fashion, lowering the value of firms that announce layoffs, and (2) almost all of the negative response occurs on the day of the announcement, suggesting that the market is not able to fully anticipate the new information, but that it responds to it very quickly.